2021
DOI: 10.1021/acsomega.1c03073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Addition of Palm Oil Biodiesel in Waste Plastic Oil on Diesel Engine Performance, Emission, and Lubricity

Abstract: This research was aimed to examine the diesel engine’s performance and emission of secondary fuels (SFs), comprising waste plastic oil (WPO) and palm oil biodiesel (POB), and to analyze their tribological properties. Their compositions were analyzed by gas chromatography–mass spectrometry (GC–MS). Five SFs (10–50% POB in WPO) were prepared by mechanical stirring. The results were compared to blank WPO (WPO100) and Malaysian commercial diesel (B10). WPO90 showed the maximum brake power (BP) and brake torque (BT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 62 publications
(188 reference statements)
0
15
0
1
Order By: Relevance
“…However, PB has been observed to be prone to oxidation, which can have a negative impact on lubricity. In their study, Awang et al (2021) found that PB had the highest COF. The oxidation process converts the esters into fatty acids such as formic acid, acetic acid, propionic acid, caproic acid and others (Fazal et al , 2013).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, PB has been observed to be prone to oxidation, which can have a negative impact on lubricity. In their study, Awang et al (2021) found that PB had the highest COF. The oxidation process converts the esters into fatty acids such as formic acid, acetic acid, propionic acid, caproic acid and others (Fazal et al , 2013).…”
Section: Introductionmentioning
confidence: 94%
“…They discovered that adding PPO to diesel lowered COF and WSD, with the least reductions of 17.62% and 19.92%, respectively, for 10% PPO in diesel. According to Awang et al (2021), polypropylene and polyethylene waste-based PPO had a lower WSD than B10 by 5.80%, although its COF was 5.44% higher. As a result, PPO could be a suitable component in PB-diesel blend to improve lubricity.…”
Section: Introductionmentioning
confidence: 99%
“…Key benefits of biodiesel are that it is neither incendiary nor volatile; it has a lower toxicity, is biodegradable, and can be recycled [245]. The emission profile of biodiesel is positive for the environment, and it has superior combustion efficacy, cetane number, flash point, and lubrication than diesel synthesized from petroleum [7,[246][247][248].…”
Section: Physical Propertiesmentioning
confidence: 99%
“…The most widely investigated biomass fuels included alcohols (methanol, 22 ethanol, 23 and n -butanol 24 ), furans (2,5-dimethylfuran 25 and 2-methyl furan 26 ), and biodiesel. 27 Compared to methanol and ethanol, n -butanol has a greater energy density and hydrophobicity. Biodiesel has similar physical and chemical properties as diesel; therefore, it can be utilized in compression-ignition engines without modification.…”
Section: Introductionmentioning
confidence: 99%